Islamic Local Awakening: Study of Muhammadiyah Renewal as The Rise of Islamic Education Identity in South Sumatera - Arif Rahman (Jurnal Pendidikan Islam, 2019)
The purpose of this study is to construct the dynamics of Muhammadiyah education in South Sumatera which is undergoing a phase called the local awakening. Such conditions occur after social, political and religious relations have struggled during the development of Muhammadiyah education there, which also helped encourage the renewal of overall Islamic education in South Sumatera. This study is a qualitative study with a social history approach. Data in the form of historical facts related to this research are collected through library and documentation techniques. The results of this study indicate that the construction of Muhammadiyah education as an identity for Islamic education in South Sumatera actually happened due to factors of Islamic renewal which occurred intensively in rural areas (periphery) that experienced a process of negotiation and integration in the social community. So that the renewal of Islam carried out by the modernist movement there actually appeared in rural areas not in urban areas as happened in other regions in Indonesia.